CAZyme from gut microbiome for efficient lignocellulose degradation and biofuel production - Chettri, Dixita; Nad, Susmita; Konar, Ujjal; Verma, Anil Kumar (Frontiers in Chemical Engineering, 2022)
Over exploitation and energy security concerns of the diminishing fossil fuels is a challenge of the present global economy. Further, negative impact of greenhouse gases released using the conventional fuels has led to the need for searching of alternative biofuel source with biomass in the form of lignocellulose coming up as among the potent candidates. The entrapped carbon source of the lignocellulose has multiple applications other than biofuel generation under the biorefinery approach. However, the major bottleneck in using lignocellulose for biofuel production is its recalcitrant nature. Carbohydrate Active Enzymes (CAZymes) are enzymes that are employed for disintegration and utilization of lignocellulose biomass as the carbon source for production of biofuels and bio-derivatives. However, cost of enzyme production and their stability and catalytic efficiency under stressed condition is a concern that hinders largescale biofuel production and utilization. Search for novel CAZymes with superior activity and stability under industrial condition has become a major research focus in this area considering the fact that the most conventional CAZymes has low commercial viability. Gut of plant eating herbivores other organisms is a potential source of CAZyme with high efficiency. The review explores the potential of gut microbiome of various organism in production of efficient CAZyme system and the challenges in using the biofuels produced through this approach as the alternative to the conventional biofuels.